Effect of vitamin D level on COVID-19 and the risk of complications in children - Kocięba-Łaciak, Anita (Pediatria Polska - Polish Journal of Paediatrics, 2023)
The immunomodulatory and pro-apoptotic role of vitamin D is still being investigated and the relationship between its deficiency and the development of many diseases is widely described. Vitamin D deficiency, which is prevalent in the world population, is under investigation, especially in the current epidemiological situation and the risk of complications from COVID-19, including multisystem inflammatory syndrome in children. Recommendations regarding the norms of vitamin D levels in children suggest monitoring of its concentration in groups at risk of deficiency and supplementation to the optimal level. Studies on the relationship of vitamin D deficiency with the severity of COVID-19 and an increased risk of complications after the disease suggest strong associations. At the same time, the literature review also noted data that indicated no or only a small effect of vitamin D on the morbidity of the studied population.